Purificação e caracterização de uma peroxidase de raízes de Moringa oleifera L e seu potencial na degradação de corantes têxteis - Almeida, Marina Gabrielle Guimarães de (2017)
Peroxidases are oxidoredutases that catalyze a variety of reactions such as reduction of hydrogen peroxide (H2O2) and oxidation of a variety of organic and inorganic compounds. These enzymes are widely distributed in nature, being produced by a variety of sources including plants, animals, and microorganisms. Class III plant peroxidases (EC 1.11.1.7) are enzymes well characterized and related to physiological events such as lignification, suberization, auxin catabolism, wound healing and plant defense. A peroxidase from roots of Moringa oleifera (named MoPOX) was purified, characterized, and its ability to degrade textile dyes was evaluated. MoPOX was purified by DEAE-Sephacel and Superdex 75, presented an apparent molecular mass of 45.6 kDa and a pI of 9.4. The optimum pH and temperature for MoPOX activity are 5.2 and 70 °C, respectively. MoPOX maintained at least 80% of its catalytic activity after incubation at 70 °C for 60 min, showing to be high thermostable. MoPOX catalytic constants showed its high affinity for guaiacol and hydrogen peroxide substrates. In addition, it can oxidize other substrates such as o-dianidisidine, eugenol and ABTS. The catalytic activity MoPOX was decreased in the presence of dithiotreitol. In contrast, Na+ and Ca2+ slightly enhanced the MoPOX enzymatic activity. Purified MoPOX (0.15, 0.03 or 0.015 mg/mL) was able to degrade different dyes (10, 25, 50 or 100 mg/L), being Remazol® Blue RGB, Remazol® Navy RGB and Telon® Turquoise M-5G 85% the most susceptible dyes. For these compounds, the decolorization rates varied from 15 to 90%, depending on the concentration dye, concentration of enzyme, and time of exposure. MoPOX is the first peroxidase purified from roots of M. oleifera. Its high termostability, plus the ability to degrade different types of textile dyes makes this enzyme a potential molecule for application in strategies for biodegradation of hazardous compounds.